Association of the extent of myocardial ischemia with outcomes in patients with suspected coronary artery disease in Japan: a cohort study. (14th October 2021) - Kato, T; Momose, M; Uemura, Y; Naya, M; Matsumoto, N; Hida, S; Yamauchi, T; Nakajima, T; Suzuki, E; Inoko, M; Tamaki, N
Abstract: Background: There is an ongoing controversy regarding the necessity of single-photon emission computed tomography (SPECT) for patients with ischemic heart diseases after the publication of the results of the ISCHEMIA trial. Purpose: We aimed to evaluate the association of the extent of myocardial ischemia with outcomes in patients with suspected coronary artery disease in Japan. Methods: From the data of 2780 patients with stable angina who were enrolled prospectively between January 2006 and March 2008 in Japan and had undergone physician-referred non-invasive imaging tests, 1205 patients managed with SPECT were stratified by 10% myocardial ischemia. Major adverse cardiac events (MACEs), including death, myocardial infarction, hospitalization for heart failure, and late revascularization, were followed-up for 1 year. Results: Patients with ≥10% myocardial ischemia (n=173) were older than patients with <10% myocardial ischemia (n=1032) and had a significantly higher 1-year cumulative incidence of MACEs (9.1% vs. 1.2%, P<0.0001). After adjusting for confounders, the risk of ≥10% myocardial ischemia relative to <10% myocardial ischemia for MACEs remained significant (adjusted hazard ratio [95% confidence interval], 2.40 [1.09–5.26], P=0.029). Conclusion: The presence of ≥10% myocardial ischemia was significantly associated with the 1-year risk for MACEs in Japanese patients with suspected coronary artery disease. Funding Acknowledgement: Type of funding sources: None.